Influence Of Distribution Of Zakat Fund On Increasing Community Welfare: (Case Study of the BUMI Baznas Program in Sukabumi Regency) - Abdul Aziz Assayuti (The Es Economics and Entrepreneurship, 2022)
Zakat is one of the pillars of Islam that must be fulfilled by every Muslim, which is the only one in the pillars of Islam that has two links, namely habluminallah and habluminannas. Zakat can also be understood as an inseparable unit in an effort to realize community welfare. During the reign of Caliph Umar bin Khattab for 10 years in various regions (provinces) that implemented Islam, the Muslims enjoyed prosperity and prosperity,The purpose of this study is to analyze the effect of the distribution of zakat funds on improving the welfare of the community.This research was conducted at DPZ BUMI Nurul Huda Rambay Wetan Mosque, Sukamantri Village, Cisaat District, which is a program from BAZNAS Sukabumi Regency. This research is a quantitative field research. The population and sample in this study were 15 respondents who were recipients of the 2019 BUMI program.data collection through questionnaires, interviews, observation and documentation. Testing data using data analysisdescriptive, validity test, normality test, significant regression test, simple linear regression analysis and hypothesis testing.The effect of the distribution of zakat funds on improving the welfare of the community is known that the positive influence between the distribution of zakat funds and the improvement of community welfare is evidenced by ry = 0.759241 and t count 4.206279 > t table 1.76131. The test results indicate that the effect of the distribution of zakat funds with the improvement of community welfare is significant.